Characterization of the heavy metal binding properties of periplasmic metal uptake protein CLas-ZnuA2. Issue 2 (19th December 2019) - Kumar, Pranav; Dalal, Vikram; Sharma, Nidhi; Kokane, Sunil; Ghosh, Dilip Kumar; Kumar, Pravindra; Sharma, Ashwani Kumar
Abstract : Candidatus Liberibacter asiaticus (CLas), a phloem-limited unculturable Gram-negative bacterium, causes citrus greening disease. Abstract : Candidatus Liberibacter asiaticus (CLas), a phloem-limited unculturable Gram-negative bacterium, causes citrus greening disease. The proteome analysis of CLas showed the presence of a heavy metal permease and Co/Zn/Cd cation exporter system. However, there is no designated metal uptake protein specific for the heavy metal permease in CLas. One of the metal uptake proteins, designated as CLas-ZnuA2, in our previous studies, showed a lower metal-binding affinity for Mn 2+ and Zn 2+ and was postulated to bind and transport metals rather non-specifically. The present study focused on the characterization of the heavy metal binding properties of CLas-ZnuA2 using SPR, CD, DSC and crystallographic studies. The crystal structure analysis of Cd 2+ bound CLas-ZnuA2 showed octahedral geometry for Cd 2+ binding as compared to a non-preferred square-pyramidal geometry for Mn 2+ and Zn 2+ binding in earlier reported crystal structures. In SPR analysis, the binding affinities of 4.7 × 10 −6 M, 7.2 × 10 −6 M, 5.3 × 10 −5 M and 4.3 × 10 −5 M for Hg 2+, Cd 2+, Ba 2+ and Co 2+ respectively were higher as compared to earlier reported values for Mn 2+ and Zn 2+ . Likewise, CD and DSC analysis showed relatively higher thermal stability for CLas-ZnuA2 on heavy metal binding. Taken together with the expression of the permease and exporter system for heavy metals, our results indicate that CLas-ZnuA2 may be involved in sequestering and transport of various transition divalent metals in environmentally stressed conditions.